Use of exogenous growth promotants in finishing cattle - Van Bibber-Krueger, Cadra (Kansas State University, 2014)
Exogenous growth promotants, such as the synthetic beta agonist zilpaterol hydrochloride (ZH), have been shown to increase carcass weight by repartitioning energy toward increased skeletal muscle at the expense of adipose tissue, which is associated with a decline in tenderness. More recently, essential oils such as menthol have been observed to have growth promoting properties in livestock. The objectives of this research were to determine effects of ZH on blood parameters and long chain fatty acids in plasma and adipose tissue, to determine if the decline in tenderness can be negated by temporary depletion of calcium during ZH supplementation, and to determine effects of crystalline menthol on blood parameters. Blood samples were collected in 7-d intervals during ZH administration. Zilpaterol hydrochloride decreased concentrations of plasma urea nitrogen and whole blood glucose (P < 0.10), but had no effects on concentrations of plasma glucose, lactate, beta-hydroxybutyrate, NEFA, or whole blood lactate (P > 0.10). Total long chain fatty acids of plasma and adipose tissue were unaffected (P > 0.10); however, ZH supplementation increased HCW, dressing percentage, and LM area (P < 0.10). Calcium was temporarily depleted during ZH supplementation in an attempt to increase tenderness of meat. No differences (P > 0.10) were observed for Warner-Bratzler shear force values, live animal performance, or carcass measurements. Addition of 0, 0.003, 0.03, 0.3% menthol (diet DM) to diets of steers resulted in a menthol × time within day interaction (P < 0.01) for IGF-1 concentration and BW; however, glucose, lactate, and PUN concentrations were unaffected (P > 0.05). Furthermore, concentrations of VFA were not different (P > 0.05), but production of fermentative gas was decreased (P < 0.01) when menthol was added at 0, 0.003, 0.03, 0.3% of substrate DM in a 24 h in vitro fermentation trial. Results from these studies suggest ZH improved efficiency of nutrient utilization for increased skeletal muscle growth; however, the decline in tenderness was not negated by the temporary depletion of calcium in the diet. Overall, ZH affected components related to increased skeletal muscle growth, but menthol did not affect blood parameters associated with growth.
Keywords: Beef cattle; Beta agonist; Growth promotant; Menthol; Animal Sciences (0475)